Soundscape analysis reveals fine ecological differences among coral reef habitats - Juan Carlos Azofeifa-Solano; Miles J.G. Parsons; Rohan Brooker; Robert McCauley; Daniel Pygas; William Feeney; Steve Simpson; Sophie L. Nedelec; Eve M. Croxford; Mark Meekan; Christine Erbe (Ecological Indicators)
Recording soundscapes in coral reef ecosystems provides an efficient, non-invasive method for ecosystem monitoring and conservation. This study assesses the ecological relevance of coral reef soundscapes, validating their utility for conservation decision-making. Using the Soundscape Code—a method that summarizes soundscape amplitude, impulsiveness, periodicity, and uniformity—we analyzed habitat differentiation across 25 simultaneous recordings from back, flat, and fore reef zones. Benthic composition analysis identified two distinct healthy habitat types: one dominated by branching corals and another without a dominant coral growth form. Acoustic analysis revealed these habitats also had unique nighttime soundscapes, driven by amplitude (loudness) and uniformity (sound diversity) differences linked to fish and invertebrate activity. This alignment between benthic structure and nocturnal soundscape patterns suggests that reef soundscapes reflect both benthic composition and the associated biological communities, including cryptic invertebrates and nocturnal fish. Our findings underscore the potential of nighttime soundscapes and the Soundscape Code as valuable tools for coral reef monitoring and management, with practical applications for ecosystem assessment and restoration planning.